Automated Ca2+ imaging of chemosensory neurones in C.elegans - Chronis, Nikos (Henry Stewart Talks, 2012)
What C. elegans are, Neuronal networks: from stimulation to behavior, Monitoring neuronal activity, Automating In vivo Ca imaging, An automated calcium imaging platform, A microfluidic chip, Processing single worms, Fabrication, Automated single worm processing on-chip, Automated calcium imaging on-chip, A typical Ca response (chemosensory neuron), Effects of age on the function of sensory neurons, Parameters, Initial intracellular Ca level may be age-dependent, Calcium pathway in ASH neuron, Using in vivo imaging for drug screening, Drug-treated vs. untreated worms
Archived at 2020/08/13